Long Noncoding RNA Interleukin 6 Antisense RNA 1 Promotes Inflammatory Effects in Lung Macrophages via Exosomes Through the S100A9/TLR4 Pathway in Chronic Obstructive Pulmonary Disease Progression - Erkang Yi; Xiaoyu Wang; Yu Liu; Zihui Wang; Ge Bai; Xinyue Mei; Fan Wu; Chengshu Xie; QiYang Li; Weitao Cao; Huahua Xu; Xinyuan Liu; et al. (MedComm)
ABSTRACT This study investigates the role of interleukin 6 antisense RNA 1 (IL6‐AS1), a highly expressed long noncoding RNA (lncRNA), in chronic obstructive pulmonary disease (COPD). An adeno‐associated virus (AAV) was used to induce the expression of IL6‐AS1 in mice, and they were exposed to cigarette smoke to establish a COPD model. IL6‐AS1‐overexpressing mice exposed to cigarette smoke demonstrated exacerbated COPD‐like pathologies. Integrated with single‐cell RNA sequencing analysis of COPD patients and pulmonary fibroblast–macrophage coculture system, our findings indicate that the upregulation of IL6‐AS1 in fibroblasts enhances the interaction between the S100A9 protein and the AGER and TLR4 receptors on lung macrophages, thereby exacerbating pulmonary inflammation. The molecular mechanism likely involves exosome‐mediated secretion, with IL6‐AS1 binding to S100A9 protein. These findings suggest that IL6‐AS1 may facilitate crosstalk between fibroblasts and macrophages, contributing to increased pulmonary inflammation, an effect that can be blocked by paquinimod. Mendelian randomization analysis further suggests a potential shared causal variant between IL6‐AS1 and COPD risk. Taken together, this investigation provides valuable insights into the function of IL6‐AS1 and its potential implications for the pathogenesis and therapeutic strategies in COPD.